PERLINDUNGAN HUKUM TERHADAP SAKSI DAN KORBAN KEJAHATAN DALAM PROSES PERADILAN PIDANA DI INDONESIA - Taufik Hidayat (Jurnal Cakrawala Hukum, 2017)
Law enforcement procedure for penal law in indoensia, statment by witnes has one of something imporent for findingthe fact in criminal case, so very importen the witnes and victim protection in procedur penal law. The establishmentof Witness and the Victim Protection Regulation is considered to be very important to protect their individual rights.The formulation of witness protection regulation is a phenomenon in the Indonesian criminal law procedure as thesub-system of penal law. The enforcement of this sub-system will always face the law enforcement officers. In theenforcement of witness protection law, it is found that the witnesses often are not under the protection. Even, theycould turn to be the victims. Thats why the formulation of the policy of witness protection program requires theharmony between the Penal Code and the Criminal Law Procedure. The witness and victim Protection laws are themagnum opus in the development of Indonesian Penal law. This law inspires the Indonesian Human Rights,especially, the witness and the victim rights in the penal law process. Thus, the witness protection program wouldbecome the standard procedures in the formulation of the Indonesian criminal law.